Request Definition Language for the User Module in the SDN Policy Engine - Lee, Seungjun; Yoon, Daegun; Oh, Sangyoon (Journal of Korean Institute of Communications and Information Sciences, 2022)
In modern warfare environment, the well defined networks becomes important to the operations. Thus, researchers study on how to use the military tactical network resources effectively. To analyze effectiveness of the results from multiple studies together, an integrated testbed is critical as well as the design and the implementation of a policy engine that performs multiple network algorithms and analyze performance simultaneously. However, when the network environment is heterogeneous, it is hard to respond adaptively to the performance indicators of the different data structures and the different execution environments of each user algorithm. To address this issue, we propose an XML-based interface format and its schema for the policy engine, which is independent from specific technologies such as programming languages and execution environments. A message from and to the policy engine and the testbed can be encoded and decoded regardless of the programming language. Furthermore, it can describe containers of the execution environment based on the Open Container Initiative standard.
Keywords: interface definition language; policy engine; testbed